The Application of a SaCoVLMTM Visual Intubation Laryngeal Mask for the Management of Difficult Airways in Morbidly Obese Patients: Case Report - Sun, Yongtao; Huang, Linlin; Xu, Lingling; Zhang, Min; Guo, Yongle; Wang, Yuelan (Frontiers in Medicine, 2021)
The intubating laryngeal mask airway (ILMA) is a supraglottic airway that facilitates ventilation and blind tracheal intubation1. The laryngeal mask airway (LMA) increases the function of the gastric drainage tube. It not only has the characteristics of low hemodynamic impact and low incidence of postoperative sore throat such as those of ordinary laryngeal masks but also has the characteristics of high sealing pressure and good ventilation effects, which effectively prevent reflux and aspiration, making it possible for wide clinical use and gradually take the place of tracheal catheters in low- and medium-risk operations2. A SaCoVLMTM visible intubation laryngeal mask combines the functions of ILMA and LMA and has an integrated optical fiber bundle that provides a view of the larynx, enabling visualization of tracheal intubation. The SaCoVLMTM visible intubation laryngeal mask was independently developed in China. It is a three-cavity laryngeal mask that provides ventilation with a visual interpolation cavity and gastric duct cavity (Fig. 1). Through the visual appliance external display screen, the laryngeal housing and tracheal intubation can be visualized, and the position of the laryngeal mask can be continuously monitored during the perioperative period. When using the ILMA, however, anesthesiologists must blindly try to optimize the position of the throat mask to meet the appropriate intubation conditions. Using SaCoVLMTM, we can directly observe the impact of standard reset operations (e.g., Chandy and "UP-Down" operations) and visually insert the tracheal intubation device. Morbidly obese people account for an increasing proportion of patients worldwide. Such patients usually have airways that are difficult to manage, exacerbating the challenges imposed by their lower functional residual capacity and consequent rapid desaturation. A safe, universal, effective and comfortable method is required to manage the airways of these patients. We report insertion of the SaCoVLMTM in three awake morbidly obese patients (BMI 46.7～49.01 kg/m2). The patients were given intravenous atropine and midazolam injections after entering the operating room and then inhaled an anesthetic with 2% lidocaine atomization. After SaCoVLMTM insertion while patients were awake, when the vocal cords were visualized, controlled anesthetic induction commenced with spontaneous ventilation.